Efeito da estimulação elétrica nervosa transcutânea (TENS) em medidas de sensibilização da dor musculoesquelética crônica e dor experimental aguda : revisão sistemática e meta-análise - Jesus, Beatriz Menezes de (2022)
Introduction: Individuals with chronic musculoskeletal pain develop changes in pain processing in the nervous system. Transcutaneous electrical nerve stimulation (TENS) is a nonpharmacological treatment for acute and chronic pain control. Amid the scope of publication on TENS in pain intensity, the importance of investigating its action in relation to sensibilization measures was highlighted. Objective: To analyze the effects of TENS for analgesia on sensitization measures in studies with chronic musculoskeletal pain and acute experimental pain. Method: The protocol was registered in PROSPERO (CRD42020213473). The guiding question of the review was: “What are the effects of TENS on indicative central and peripheral sensibilization measures in chronic musculoskeletal pain and acute experimental pain at any point in time, compared to placebo TENS?”, having the acronym PICOT as P: chronic musculoskeletal pain and pain induced in healthy individuals; I: TENS; C: placebo; O: primary and secondary hyperalgesia, temporal summation, conditioned pain modulation, pain intensity at rest and in motion; T: any time. The search was performed in the databases CENTRAL, CINAHL, EMBASE, LILACS via BVS, PEDro, PubMed, Science Direct, Web of Science and gray literature in Google Scholar and manual search. Without language or year of publication restriction. Randomized clinical trials in adults with chronic musculoskeletal pain or healthy adults with induced pain that offered active TENS and placebo, as well as pain assessment, were included. Two researchers independently performed the data extraction, and a third researcher was responsible for analyzing the discordances. The level of agreement was assessed by the Kappa test. For the risk of bias, we followed the Cochrane Collaboration Risk of Bias Scale. The meta-analyses were performed using the Review Manager statistical software with analysis of the outcomes and the subgroups of frequency, time and intensity. The uncertainty around the evidence was assessed using the GRADE classification. Results: From 22.252 manuscripts found, 58 studies were selected, 22 of which with chronic musculoskeletal pain and 36 with induced pain in healthy individuals. The inclusion and exclusion of the studies by the researchers had a high level of agreement (Kappa > 0.92). Thirty-four studies assessed pain intensity; 24 studies investigated hyperalgesia; temporal summation was only evaluated in two studies; and conditioned pain modulation was not observed in the included studies. The studies demonstrated a high risk of bias in relation to sample size. The meta-analyses favored TENS, despite its limitations and heterogeneity. Primary hyperalgesia in studies with musculoskeletal pain presented a high level of evidence, while other outcomes in both studies (chronic musculoskeletal pain and acute experimental pain) presented moderate evidence. It is not possible to infer results about temporal summation and conditioned pain modulation. Conclusions: Moderate evidence suggests that TENS promotes analgesia by reducing central and peripheral sensibilization, as evidenced by the reduction in primary hyperalgesia, secondary hyperalgesia, pain intensity at rest and on motion in the experimental acute pain and chronic musculoskeletal pain.